Fabrication of Polyethylene Glycol‐Based Hydrogel Microspheres Through Electrospraying. Issue 8 (9th April 2015) - Jain, Era; Scott, Kayla M.; Zustiak, Silviya P.; Sell, Scott A.
<x xml:space="preserve">Abstract</x> Polyethylene glycol (PEG) hydrogel microspheres of controlled sizes and narrow size distribution were fabricated via electrospraying. To facilitate the formation of microspheres through electrospraying, the gelation time of PEG hydrogels by Michael's addition reaction between acrylate and thiol were optimized. The effect of electrospraying parameters such as applied voltage, flow rate, needle gauge, and tip to collector distance (TTCD) on Taylor cone formation and microsphere size and distribution was determined. Applied voltage and TTCD had the strongest influence on Taylor cone formation and microsphere size and distribution. By careful design of process parameters a wide range of PEG hydrogel microspheres were obtained, namely 70–700 μm in diameter. The biodegradable PEG hydrogel microspheres developed in this study through a combination of mild gelation chemistry and electrospraying will be valuable in a variety of biological applications including drug and protein delivery, cell encapsulation, and biosensors.<inline-graphic xlink:href="ark:/27927/pgj2c6hwcw8" content-type="mame201500058-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />